Child Criminal Justice System in Islamic Law and the Convention on the Rights of the Child: A Comparative Study Between Indonesia, Iran, and Pakistan - Siswanto, Moh. Aris (KnE Social Sciences, 2025)
This study examines the dynamic interaction between Islamic law principles and the Convention on the Rights of the Child (CRC) in the juvenile criminal justice system, with a comparative study focusing on Indonesia, Iran, and Pakistan. Islamic law, through the concepts of bulugh and Ta’zir, aims at the correction and improvement (ishlah) of minors. The CRC, on the other hand, sets a standard age of 18 years, prohibits the death penalty/life imprisonment, and encourages rehabilitation, diversion, and non-custodial treatment. Using descriptive-comparative and analytical-normative legal methods, the study analyzes the laws and practices of the three countries. The results show significant variations: Indonesia has been relatively successful in integrating the values of the CRC and Islamic Law in the 2012 Juvenile Justice Act, prioritizing diversion and training. In contrast, Iran faces serious conflict because the Shia interpretation allows hudud and qisas punishments for children under 18, leading to executions in contravention of the CRC. Pakistan, despite having progressive legislation ( JJSA 2018) in line with the CRC, has shown poor implementation, characterized by inconsistent definitions of children, inhumane treatment by authorities, minimal diversion, and poor conditions of excluded facilities. The discussion underlines that harmonization of these two legal frameworks is highly dependent on flexible interpretation and effective implementation. As a suggestion, Indonesia needs to continue to improve the SPPA Law. Iran should reform its laws to abolish the death penalty for children and align the age of responsibility. Pakistan urgently needs drastic improvements in standardizing the definition of children, improving remote conditions, and training law enforcement officers to realize comprehensive child rights protection.